Effect Of Junction Quality On The Performance Of A Silicon Solar Cell - Zerbo, I.; Zoungrana, M.; Ouedraogo, A.; Bathiebo, D. J. (University of Eloued جامعة الوادي, 2017)
In this work, a modeling study of the effect of the junction quality on the performance of a silicon solar cell is presented. Based on a one dimensional modeling of the solar cell, the continuity equation of excess minority carriers is solved with boundary conditions taking into account the intrinsic junction recombination velocity and led to analytical expressions of photocurrent density, photovoltage and electric power. The effect of the intrinsic junction recombination velocity or the solar cell junction quality on photocurrent, photovoltage and electric power, is exhibited and we determine the maximum electric power, the junction dynamic velocity at the maximum power point and the conversion efficiency according to the junction quality of the solar cell. From the electric power lost at the junction, we calculated the shunt resistance of the solar cell according to the junction quality.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 02
Keywords: Efficiency; Intrinsic junction recombination velocity; Joule effect; Solar cell; Shunt resistance.